Effect of a focusing electric field on the formation of arc generated carbon nanotubes - Karmakar, Soumen; Nagar, Harshada; Pasricha, R.; Seth, T.; Sathe, V. G.; Bhoraskar, S. V.; Das, A. K. (Nanotechnology, 2006)
The effect of a focusing electric field on the formation of carbon nanotubes in a direct current arc-plasma is investigated. The hard deposits on the surface of the cathode are the main products, rich in multi-walled carbon nanotubes. It is seen that the focusing electric field has a distinct influence on the yield, purity and morphology of the nanotubes. The yield of the carbon nanotubes under the `focused field condition' has been found to be higher than that derived from the normal electrode configuration. It has been observed that the deposition of carbonaceous soot on the reactor wall is considerably reduced on application of the focusing electric field. Transmission electron microscopy has been used to determine the morphology of the nanotubes. In addition, Raman spectroscopy has helped in distinguishing the graphene-like structures from the disordered carbon networks and helped in analysing the morphology of the tubes. Thermal analysis gave a qualitative estimation of the relative yield of carbon nanotubes within the cathode deposits and their thermal stabilities. The crystalline nature of the samples has been confirmed by x-ray diffraction analysis. The results clearly indicate that the focusing electric field confines the positively charged carbon precursors within the cathode-anode space causing high relative yield and purity and has a distinct effect on controlling the inner diameter of the as-synthesized carbon nanotubes.

In situ optical emission spectroscopic investigations during arc plasma synthesis of iron oxide nanoparticles by thermal plasma - Banerjee, Indrani; Joshi, N. K.; Sahasrabudhe, S. N.; Kulkarni, Naveen V.; Karmakar, Soumen; Pasricha, R.; Ghorui, S.; Tak, Atul K.; Murthy, Shri P. S. S.; Bhoraskar, S. V.; Das, A. K. (IEEE Transactions on Plasma Science, 2006)
Investigations using in situ precursor spectroscopy during the growth of nanoparticles of iron oxide by thermal plasma induced gas phase condensation method have been shown to be useful for correlating the size of nanoparticles with existing plasma parameters. The relative abundance of ionized Fe species inside the plasma plume is seen to directly establish the relation between particle size, arc current, arc length, and ambient pressure of the reacting oxygen gas. The argon plasma from a transferred arc reactor is made to impinge on the anode that is allowed to vaporize and react with oxygen. The spectral line profiles of both Ar and Fe along the plasma column during the synthesis of nanoparticles have been proved to be useful in understanding the growth mechanism. Band intensities of FeO molecular states indicated the inverse relation with particle sizes that have been correlated to the two competitive processes in which energy is released, namely: 1) one involving the radiative transition and 2) the other that of the growth by coagulation. Atomic Boltzmann plots are used for estimating the temperatures of the zones, whereas particle sizes have been inferred using transmission electron microscopic measurements.
Keywords: plasma arc device; plasma-materials processing applications; spectroscopy

Mossbauer spectroscopic investigations of nanophase iron oxides synthesized by thermal plasma route - Nagar, Harshada; Kulkarni, Naveen V.; Karmakar, Soumen; Sahoo, B.; Banerjee, Indrani; Chaudhari, P. S.; Pasricha, R.; Das, A. K.; Bhoraskar, S. V.; Date, Sadgopal K.; Keune, W. (Materials Characterization, 2008)
Magnetic nanoparticles of iron oxide were synthesized by transferred arc plasma induced gas phase condensation method. Structural, morphological and magnetic studies of the as synthesized powder were carried out using X-ray diffraction, transmission electron microscopy and Mossbauer spectroscopy. These studies have revealed the simultaneous nucleation and condensation of different magnetic phases with a broad size distribution of the nanoparticles which is peaked at 30-50 nm and ranges from 10 nm to 80 nm. 57 Fe Mossbauer spectra recorded at various temperatures (5 K-300 K) in presence of external magnetic field (at 5 K) have suggested the presence of different phases of iron oxide with sizable amounts of gamma-Fe2O3 and alpha-Fe2O3 in addition to Fe3O4. The relative concentrations of these phases have been obtained by a self consistent spectral area analysis and were found to be 44:22:34 (%). (C) 2007 Elsevier Inc. All rights reserved.
Keywords: iron oxides; Mossbauer spectroscopy; phase analysis; plasma synthesis